Violation of Stokes–Einstein and Stokes–Einstein–Debye relations in polymers at the gas-supercooled liquid coexistence. (5th November 2020) - Singh, Jalim; Jose, Prasanth P
Abstract: Molecular dynamics simulations are performed on a system of model linear polymers to look at the violations of Stokes–Einstein (SE) and Stokes–Einstein–Debye (SED) relations near the mode coupling theory transition temperature T c at three (one higher and two lower) densities. At low temperatures, both lower density systems show stable gas-supercooled-liquid coexistence whereas the higher density system is homogeneous. We show that monomer density relaxation exhibits SE violation for all three densities, whereas molecular density relaxation shows a weak violation of the SE relation near T c in both lower density systems. This study identifies disparity in monomer mobility and observation of jumplike motion in the typical monomer trajectories resulting in the SE violations. In addition to the SE violation, a weak SED violation is observed in the gas-supercooled-liquid coexisting domains of the lower densities. Both lower density systems also show a decoupling of translational and rotational dynamics in this polymer system.